Volumetric locking free 3D finite element for modelling of anisotropic visco-hyperelastic behaviour of anterior cruciate ligament. (17th May 2018) - Bijalwan, Ashutosh; Patel, B.P.; Marieswaran, M.; Kalyanasundaram, Dinesh
Abstract: Solids such as polymers, soft biological tissues display visco-hyperelastic, isochoric and finite deformation behaviour. The incompressibility constraint imposed severe restriction on the displacement field results in volumetric locking. Many techniques have been developed to address the issue such as reduced integration, mixed formulation, B-Bar and F-Bar methods, each of them with their own merits and demerits. In this work, we have developed a 3D finite element (hereby referred as J-Bar method) to counter volumetric locking in visco-hyperelastic solids. To validate the proposed J-Bar method, rheological characteristics of the human anterior cruciate ligament (ACL) were predicted and compared with the experimental results.